Open-label, phase IIa study of dabrafenib plus trametinib in East Asian patients with advanced BRAF V600-mutant cutaneous melanoma. (August 2020) - Si, Lu; Zhang, Xiaoshi; Shin, Sang Joon; Fan, Yun; Lin, Chia-Chi; Kim, Tae Min; Dechaphunkul, Arunee; Maneechavakajorn, Jedzada; Wong, Chi Sing; Ilankumaran, Palanichamy; Lee, Dung-Yang; Gasal, Eduard; et al.
Abstract: Purpose: This study (NCT02083354) assessed the efficacy and safety of dabrafenib plus trametinib in East Asian patients with advanced BRAF V600-mutant cutaneous melanoma. Method: Overall, 77 patients of East Asian origin (including 61 from Mainland China) with unresectable or metastatic BRAF V600-mutant cutaneous melanoma were enrolled. Prior treatment was allowed except with BRAF/MEK inhibitors. Patients received dabrafenib 150 mg twice daily and trametinib 2 mg once daily. The primary end-point was objective response rate (ORR) using Response Evaluation Criteria in Solid Tumours 1.1. Secondary end-points were duration of response (DOR), progression-free survival (PFS), overall survival (OS), pharmacokinetics and safety. Results: At data cutoff (February 23, 2018; median follow-up, 8.3 months), treatment was ongoing in 36 patients (47%). The median age was 52 years; 32% of patients had elevated lactate dehydrogenase, and 84% had received prior systemic therapy. ORR was 61% (95% confidence interval: 49.2–72.0), with four patients (5%) achieving complete response. Median DOR and PFS were 11.3 and 7.9 months, respectively. Median OS was not reached. The most common adverse event (AE) of any grade was pyrexia (56%). Grade ≥III AEs occurred in 29 patients (38%). The most common grade ≥III AEs were pyrexia (8%) and anaemia (6%). AEs led to permanent discontinuation in five patients (6.5%). Mean Cmax for dabrafenib and trametinib was 3560 and 11.5 ng/mL (day 1) and 2680 and 27.1 ng/mL (day 15), respectively. Conclusion: These results support the efficacy and tolerability of dabrafenib in combination with trametinib in East Asian patients with unresectable or metastatic BRAF V600-mutant cutaneous melanoma. Highlights: Dabrafenib-trametinib was efficacious in East Asians with advanced BRAF V600-mutant cutaneous melanoma. Efficacy and safety of dabrafenib-trametinib in East Asians was similar to global studies. No new safety findings were observed with dabrafenib-trametinib in East Asian patients. Dabrafenib-trametinib could be a treatment option for East Asians with BRAF V600-mutant melanoma.